2013
DOI: 10.1007/s10461-013-0583-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Alcohol Use, Other Psychosocial Factors, Structural Factors and Antiretroviral Therapy (ART) Adherence Among South African ART Recipients

Abstract: We examined whether alcohol use is associated with antiretroviral therapy (ART) adherence independently of structural and psychosocial factors among 304 male and female ART recipients in ART sites in Tshwane, South Africa. ART adherence was assessed by the CASE Adherence Index. Independent variables were demographic, structural, psycho-social, and alcohol use (AUDIT score) factors. In hierarchical multiple regression, demographic variables (Step 1) explained 4 % of variance in ART adherence (p ≤ 0.01). Varianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 11 publications
5
62
0
Order By: Relevance
“…Six investigations found that stigma was significantly associated with poor self-reported adherence at the multivariate level, after adjusting for factors such as demographics, perceived health, structural barriers, and alcohol and drug use [42,44,45,47,49,56]. Two prospective investigations lent support to this association as well.…”
Section: Studies That Combined Multiple Dimensions Of Stigmamentioning
confidence: 93%
See 2 more Smart Citations
“…Six investigations found that stigma was significantly associated with poor self-reported adherence at the multivariate level, after adjusting for factors such as demographics, perceived health, structural barriers, and alcohol and drug use [42,44,45,47,49,56]. Two prospective investigations lent support to this association as well.…”
Section: Studies That Combined Multiple Dimensions Of Stigmamentioning
confidence: 93%
“…However, multivariate and mediational analyses differed, so both were retained for the review. An additional two studies [44,45] reported on the same dataset, but different adherence outcomes were used in analyses, so both were retained.…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol use was associated with non-adherence to antiretroviral therapy among HIV infected people in Pwani Region, eastern Tanzania [45]. Likewise, study done in South Africa showed that alcohol use is independently associated with antiretroviral adherence [46]. Study done in South India also indicated the association of alcohol use with non-adherence [47].…”
Section: Alcohol Drinkers and Non-adherence To Antiretroviral Therapymentioning
confidence: 94%
“…We will recruit participants from each site without an attempt to have equal numbers of men and women; we anticipate a ratio of about 2:1 females to males. Based on our prior data [44], we would estimate that about 40% of ART recipients will be alcohol drinkers. Of the alcohol drinkers, we estimate that about 15% would meet the criterion related to alcohol (have six (or four, if female) or more drinks on one occasion at least weekly, and score no more than 22 on the AUDIT).…”
Section: Methodsmentioning
confidence: 99%